Factor shares, inequality and capital flows (2015)
We present an endogenous growth model where innovations are factor savingand model the choice of technologies in an Overlapping Generations framework.Markets are competitive and factor prices are determined by marginal productiv-ity of factors; therefore, the income share of reproducible factors increases withthe stage of development. Beyond the standard results of this type of model wefind that (i) without bequests long run growth is not possible, (ii) if the economypresents long run growth then intra generation inequality may last forever but ifthe economy does not present long run growth then in steady state there is no intrageneration inequality (iii) when the economy is open, the pattern of capital flowsdepends not only on the relative abundance of factors but also on the technolo-gies and, for this reason, capital may not flow from rich to poor economies (iv)consistently, capital flows may not help to break poverty traps.